Electronic structure and properties of transition metal compounds : theory and applications - Bersuker, I. B.; Liu, Yang (John Wiley & Sons, Inc., 2025)
"Transition metals commonly refers to 40 chemical elements (21-30, 39-48, 71-80, and 103-112) which represent the transition between group 2 and group 13 elements, are solids at room temperature (except mercury), tend to have high tensile strength, density, and melting and boiling points. Distinguished from pure metallic state with electronic band structures, transition metal elements form a large variety of coordination compounds with an incomplete d-electron subshell leading to different oxidation states, and other special properties. They form also coordination centers in a wide range of atomic formations including important metalo-biochemical centers, activation states of chemical reactions, and serve as good homogeneous or heterogeneous catalysts. Areas of applications of transition metal compounds are innumerable"--